2019
DOI: 10.1126/sciadv.aau9060
|View full text |Cite
|
Sign up to set email alerts
|

Cell-based screen identifies a new potent and highly selective CK2 inhibitor for modulation of circadian rhythms and cancer cell growth

Abstract: We discovered a new CK2 inhibitor and revealed its mechanism of action, connecting the circadian clock and cancer regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 62 publications
2
79
0
1
Order By: Relevance
“…This likely provides a mechanism for the enhanced selectivity of most CLK1/2/4 inhibitors over closely-related CLK3. It is interesting to note that the most selective inhibitors including the casein kinase 2 alpha 1 (CK2α1) inhibitor GO289 47 , the dual PIM/DAPK3 inhibitor HS56 48 , the selective DAPK3 inhibitor HS94 and HS184 48 and the CLK inhibitor MU1210 27 do not significantly interact with the hinge back bone, but rather engage contacts at the back pocket particularly with the DFG-1 residue. Such binding modes have also been noted by the KLIFS database 49 .…”
Section: Resultsmentioning
confidence: 99%
“…This likely provides a mechanism for the enhanced selectivity of most CLK1/2/4 inhibitors over closely-related CLK3. It is interesting to note that the most selective inhibitors including the casein kinase 2 alpha 1 (CK2α1) inhibitor GO289 47 , the dual PIM/DAPK3 inhibitor HS56 48 , the selective DAPK3 inhibitor HS94 and HS184 48 and the CLK inhibitor MU1210 27 do not significantly interact with the hinge back bone, but rather engage contacts at the back pocket particularly with the DFG-1 residue. Such binding modes have also been noted by the KLIFS database 49 .…”
Section: Resultsmentioning
confidence: 99%
“…REV-ERB and ROR proteins compete for response element (RORE)/ Clock/Bmal1 transcription to control a new transcriptional cycle for nearly 24 h 21 Furthermore, it has been reported that circadian oscillations can be post-transcriptionally modified by casein kinase 1/2 (CK1/2) via the phosphorylation of PER2. 22,23 For example, CK1δ/ε is a priming kinase for PER2 phosphorylation and a Discordant mouse model caused by CK1δ/ε disruption in GABAergic neurons shows a long (27.4 hour) behavioral period. 24 Hence, the current view is that circadian rhythms are governed by a very complex system that works in a well-organized way to coordinate endogenous circadian rhythms in gene expression and physiological metabolism.…”
Section: Circadian Clocksmentioning
confidence: 99%
“…Main off-targets of silmitasertib (1) reported to have antiproliferative effects are for example the cyclin-dependent kinase (CDK1) [43,44], PIM-1 protooncogene, serine/threonine kinase (PIM1) [45], Homeodomain-interacting protein kinase 3 (HIPK3) [46,47], TANK-binding kinase 1 (TBK1) [48] or FMS-like tyrosine kinase 3 (FLT3) [49,50]. More recently some more selective CK2 inhibitors have been reported, including GO289 by Oshima et al [51] or an allosteric inhibitor CAM4066 by Brear et al [18]. However, the allosteric inhibitors are still weak and would require optimization and the selectivity of GO289 has not been comprehensively assessed.…”
Section: Conclusion/discussionmentioning
confidence: 99%